2009
DOI: 10.1159/000260086
|View full text |Cite
|
Sign up to set email alerts
|

Xolair Is Effective in Allergics with a Low Serum IgE Level

Abstract: Background: Two atopic patients suffering from severe allergy difficult to handle by conventional medication were given Xolair despite an IgE level <30 kU/l. Methods: Increasing dosages were given and monitored by clinical evaluation and CD-sens to clinically relevant allergens. The patients’ IgE antibody fractions were 11–14%. Results: Xolair dosages extrapolated from a recommended dose for IgE of 30–75 kU/l were adapted to the patients’ IgE body pool but had very little effect. The double dose resulted in so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…SCIT had to be stopped for one of our patients due to uncontrolled asthma. To better understand why SCIT failed in this patient despite pre‐treatment with omalizumab, it would have been interesting to assess the patient's HDM specific IgE‐antibody fraction (specific IgE‐ab/Total IgE) and CD‐sens to HDM . Closer monitoring and a possible increase in the omalizumab dosage might have allowed SCIT to be continued.…”
Section: Discussionmentioning
confidence: 99%
“…SCIT had to be stopped for one of our patients due to uncontrolled asthma. To better understand why SCIT failed in this patient despite pre‐treatment with omalizumab, it would have been interesting to assess the patient's HDM specific IgE‐antibody fraction (specific IgE‐ab/Total IgE) and CD‐sens to HDM . Closer monitoring and a possible increase in the omalizumab dosage might have allowed SCIT to be continued.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Wahn et al (15) and Bousquet et al (14) reported that response to omalizumab is not predicted by total IgE. Ankerst et al (16) reported that omalizumab is effective for patients with severe asthma with a low total serum IgE level and positive for SPT and allergen threshold sensitivity.…”
Section: Case Studymentioning
confidence: 99%
“…However, previous studies show good correlations between CD-sens to peanut and clinical allergy to peanut, that is objective symptoms in DBPCFC [22,24]. The correlation between CD-sens and clinical allergen sensitivity has been used, in previous studies, to identify omalizumab responders as well as to evaluate treatment efficacy after omalizumab dose adjustments [20,21,32]. Measurements of basophil allergen threshold sensitivity, for example CD-sens, have been shown to correlate significantly with the outcome of bronchial, nasal allergen titration challenge and oral challenges [22,23,[29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Omalizumab has also been used as a 'pre-treatment' for specific immunotherapy of perennial aeroallergens resulting in fewer systemic allergic reactions and more patients reaching the maintenance dose compared to placebo [18]. Previous studies suggest that dosing should be individualized and that treatment effect has to be monitored [20,21]. Besides, among peanut allergic children, pre-treatment with omalizumab before peanut OIT has shown to be effective [19].…”
Section: Introductionmentioning
confidence: 99%